Escolha de instituições de educação superior e carreiras: um estudo sobre o que pretendem estudantes de grupos sociais privilegiados - Monção, Carolina Ferrucci (2009)
This work points out the ways and results of an investigation about the choices intended by students from privileged social groups of Mogi das Cruzes (SP) towards superior education: institutions and careers. The main objective of the research, over all based on Pierre Bourdieu s notions of social position, economical and cultural capital, has related the cultural practices of students who are finishing high school at expensive schools to their intentions of choice of institutions and careers at college. In order to reach this objective, three schools that charged the highest high school fees at the referred municipal district were selected. After contacting the schools, two of them accepted that their students answered the instrument of data collect, a questionnaire elaborated for this specific purpose. The questionnaire had 74 objective and subjective questions and it was answered by 77 students from the two schools in 2008. The analysis of the results quantified the students cultural practices museums visits, physical activities developed by them, foreign language fluency, informatics knowledge, arts courses, musical instruments abilities, international trips and related them to these students intentions of going to college. 75 out of 77 subjects involved on this investigation stated their intentions to go to college. The results about parental formation and occupation, family income, types of investments on the cultural practices cited above mark the possibility of these students being part of privileged social groups not only through an economical point of view. The results also point out the fact that the various practices accomplished by the students are related to a vast series of options towards the intended institutions